2020
DOI: 10.21608/aadj.2020.118233
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Different Preparation Designs on Fracture Resistance of Full-Coverage Occlusal Veneers After Thermo-Mechanical Aging Simulation

Abstract: Aim: To evaluate the fracture resistance maxillary molars restored with lithium disilicate glass-ceramic (LDG) occlusal veneers with two preparation designs. Subjects and methods: Twenty extracted maxillary molars were assigned to two groups (n = 10). In group 1 (GROUP S), the teeth received a preparation for a conservative fullcoverage occlusal veneer restoration with a 90 rounded shoulder margin. In group 2 (GROUP c), were prepared with a minimally invasive chamfer. LDG restorations (IPS e.max CAD) were obta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…(23,24) Fracture resistance test was chosen in our study as it played a crucial role in determining the longevity of the restorations. (21) Regarding the effect of the preparation design on fracture resistance of occlusal veneers in our study, the type of the preparation design had non-significant effect and that might be because the point of loading during fracture resistance test was centralized on specimens away from the finish line. (25) Our results agreed with Abdelhameed et al (2018) (5) and Emam Z and Aleem N. (2020) (7) who found that there was no effect of the preparation design on occlusal veneers fracture resistance .…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…(23,24) Fracture resistance test was chosen in our study as it played a crucial role in determining the longevity of the restorations. (21) Regarding the effect of the preparation design on fracture resistance of occlusal veneers in our study, the type of the preparation design had non-significant effect and that might be because the point of loading during fracture resistance test was centralized on specimens away from the finish line. (25) Our results agreed with Abdelhameed et al (2018) (5) and Emam Z and Aleem N. (2020) (7) who found that there was no effect of the preparation design on occlusal veneers fracture resistance .…”
Section: Discussionmentioning
confidence: 65%
“…(17) For standardization of occlusal veneer restorations, CAD/CAM technology was used to standardize the thickness and the anatomy of the restorations and to avoid laboratory errors. (21) Adhesive resin cement was chosen in our study as it was found that all ceramic restorations cemented using adhesive resin cements had greater fracture resistance than those cemented using traditional cements. (22) Moreover, in our study we used total etch technique because it was reported that the use of total-etch technique enhanced the bond strength up to 28 MPa within enamel and 13-20 MPa within dentin that lead to improving the fracture resistance.…”
Section: Discussionmentioning
confidence: 99%
“…(41) Regarding the preparation design, it was recommended to decrease the incisal part to evenly distribute the load and lower the stress levels on the veneer material. (41) In their study, Hassan et al (2020) (42) employed the Thermo Mechanical Load Cycling procedure to evaluate the maxillary molars fracture resistance repaired with occlusal veneers constructed of Lithium Disilicate Glass-ceramic. The researchers also compared the outcomes of two distinct preparation designs.…”
Section: Discussionmentioning
confidence: 99%
“…The utilization of a minimally invasive occlusal veneer preparation, along with a marginal chamfer, demonstrated encouraging fracture resistance outcomes that were comparable to those achieved with a conventional conservative preparation for the repair of molars utilizing CAD/CAM lithium disilicate occlusal veneers. (42) Zhang et al (2020). (10) analyzed different types of preparation designs in premolars, including occlusal veneers and occlusal veneers with covering on the lingual and proximal surfaces.…”
Section: Discussionmentioning
confidence: 99%